Prognostic factors for relapse in resected gastroenteropancreatic neuroendocrine neoplasms: A systematic review and meta-analysis. (December 2021) - Broadbent, Rachel; Wheatley, Roseanna; Stajer, Sabrina; Jacobs, Timothy; Lamarca, Angela; Hubner, Richard A; Valle, Juan W; Amir, Eitan; McNamara, Mairéad G
Highlights: There is a significant risk of relapse after potentially curative resection of a GEP-NEN. Systematic review and meta-analysis conducted to factors prognostic for relapse. Multivariable pooled analyses identified factors prognostic for worse relapse free survival. Factors prognostic for relapse should be considered in follow-up imaging protocols. Future trials of adjuvant treatment could incorporate these factors in stratification criteria. Abstract: Background: Gastroenteropancreatic neoplasms (GEP-NENs) can potentially be cured through surgical resection, but only 42–57% achieve 5-year disease-free survival. There is a lack of consensus regarding the factors associated with relapse following resection of GEP-NENs. Methods: A systematic review identified studies reporting factors associated with relapse in patients with GEP-NENs following resection of a primary tumour. Meta-analysis was performed to identify the factors prognostic for relapse-free survival (RFS) or overall survival (OS). Results: 63 studies comprising 13, 715 patients were included; 56 studies reported on pancreatic NENs (12, 418 patients), 24 reported on patients with grade 1–2 tumours (4, 735 patients). Median follow-up was 44.2 months, median RFS was 32 months. Pooling of multivariable analyses of GEP-NENs (all sites and grades) found the following factors predicted worse RFS (all p values < 0.05): vascular resection performed, metastatic disease resected, grade 2 disease, grade 3 disease, tumour size > 20 mm, R1 resection, microvascular invasion, perineural invasion, Ki-67 > 5% and any lymph node positivity. In a subgroup of studies comprising exclusively of grade 1–2 GEP-NENs, R1 resection, perineural invasion, grade 2 disease, any lymph node positivity and tumour size > 20 mm predicted worse RFS (all p values < 0.05). Few OS data were available for pooling; in univariable analysis (entire cohort), grade 2 predicted worse OS (p = 0.007), while R1 resection did not (p = 0.14). Conclusions: The factors prognostic for worse RFS following resection of a GEP-NEN identified in this meta-analysis could be included in post-curative treatment surveillance clinical guidelines and inform the stratification and inclusion criteria of future adjuvant trials.